Pengembangan LKPD Digital Berbasis Problem Based Learning Berbantuan Canva untuk Meningkatkan Kemampuan Berpikir Matematis Siswa - Gustinah, Gustinah; Risnanosanti, Risnanosanti; Fitriani, Afriza (JOEAI (Journal of Education and Instruction), 2026)
This study aims to produce and describe Digital LKPD based on Problem Based Learning (PBL) to facilitate the creative thinking skills of vocational high school students. This study is a type of research on the development of Digital LKPD based on Problem Based Learning assisted by Canva. The validation results of Digital LKPD on the material aspect reached 74% and on the design aspect obtained 71.62% with a valid category. The results of the practicality test of Digital LKPD by mathematics teachers obtained 95% and the results of the practicality test by students reached 86.36% in the practical category. The results of the effectiveness test by students were 83.33% and the results of the creative thinking ability test showed that there was an increase in students' creative thinking abilities after using Digital LKPD in the learning process. This study produced Digital LKPD based on Problem Based Learning that can facilitate the creative thinking abilities of vocational high school students on permutation material with the help of Canva which can be easily accessed by students. Student worksheets presented in Digital LKPD use a PBL framework using creative thinking indicators Focus on Problems, Cooperation, Design, and Understanding. In conclusion, the quality of this digital worksheet was assessed based on three aspects of suitability: validity, practicality, and effectiveness. Therefore, this digital worksheet based on PBL education, supported by Canva, is suitable for use.   Keywords: Creative Thinking, Digital Worksheet, PBL